2019
DOI: 10.1002/chir.23053
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of a new open‐tubular capillary column for enantioseparation by capillary electrochromatography

Abstract: In order to use the enantioseparation capability of cationic cyclodextrin and to combine the advantages of capillary electrochromatography (CEC) with opentubular (OT) column, in this study, a new OT-CEC, coated with cationic cyclodextrin (1-allylimidazolium-β-cyclodextrin [AI-β-CD]) as chiral stationary phase (CSP), was prepared and applied for enantioseparation. Synthesized AI-β-CD was characterized by infrared (IR) spectrometry and mass spectrometry (MS). The preparation conditions for the AI-β-CD-coated col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…With the increase of buffer solution pH, the amount of Si–OH dissociation and zeta potential increase, which led to the increase of EOF 47 . The EOF of MDI‐β‐CD‐modified COF‐coated OT column was smaller than that of the bare capillary column owing to the blocking of silanol 48 . It may be that the formation of EOF in MDI‐β‐CD‐modified COF‐coated OT column was mainly attributed to the dissociation of –NH 3 + on the surface of MDI‐β‐CD‐modified COF.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the increase of buffer solution pH, the amount of Si–OH dissociation and zeta potential increase, which led to the increase of EOF 47 . The EOF of MDI‐β‐CD‐modified COF‐coated OT column was smaller than that of the bare capillary column owing to the blocking of silanol 48 . It may be that the formation of EOF in MDI‐β‐CD‐modified COF‐coated OT column was mainly attributed to the dissociation of –NH 3 + on the surface of MDI‐β‐CD‐modified COF.…”
Section: Resultsmentioning
confidence: 99%
“…All of them were completely separated with separation factors ( α ) > 1.05 (Table 1). 48 However, labetalol contains two chiral centers, and four stereoisomers should have been separated. But according to the separation of other β‐blockers in Figure 6, only the hydroxyl chiral center was separated, and the carbon chiral center was not separated in labetalol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Meanwhile, molecular stereo configuration affected the resolution of chiral enantiomers. 31 For example, fipronil have two aromatic rings, which may fit better in the CD cavity; the presence of hydroxyl or carbonyl groups in histidine can enhance the hydrogen bond interaction between hydroxyl groups of CD and histidine. 32 The results showed that all the analytes could be rapidly separated from the baseline under the optimized conditions of Method 2 with a resolution > 1.5 and a separation factor (α) > 1.05 (Table 2).…”
Section: Enantioseparation Performance Of Cof Tpbd-coated Ot Columnmentioning
confidence: 99%
“…The β‐CD and derivatives have attracted extensive attentions and been used as the most popular chiral selectors in CEC , because they have the advantages of inexpensive, providing a fast equilibration of the CD‐solute complex, high efficiency, and a better peak symmetry . Guo et al.…”
Section: Open‐tubular Capillary Electrochromatographymentioning
confidence: 99%